Quality standards for passenger trains: Political majorities and environmental costs - Julia Rothbauer; Gernot Sieg (Technische Universität Braunschweig, Institut für Volkswirtschaftslehre, 2010)
This study analyzes the minimum quality standard set by the European Union (EU) through Regulation 1371/2007 of Rail Passengers' Rights and Obligations. A welfare maximizing quality standard raises quality and consumer satisfaction, but does not improve the modal split of rail transport. A minimum quality standard determined by political majorities may or may not increase welfare. However, all binding standards induce travelers to switch to transport modes with higher anthropogenic greenhouse gas emissions.
Keywords: L51; L92; D72; 330; regulation; minimum quality standards; median; rail; Eisenbahnpersonenverkehr; Qualitätsmanagement; Normung; Kundenzufriedenheit; Wohlfahrtseffekt; Verbraucherschutz; EU-Verkehrspolitik